Universal primers for rift valley fever virus whole-genome sequencing - Kwan Woo Kim; Banseok Lee; Sujeong Eom; Donghoon Shin; Changwoo Park; Seil Kim; Hana Yi (Scientific Reports, 2023)
Abstract Rift Valley fever (RVF) is a mosquito-borne zoonotic disease causing acute hemorrhagic fever. Accurate identification of mutations and phylogenetic characterization of RVF virus (RVFV) require whole-genome analysis. Universal primers to amplify the entire RVFV genome from clinical samples with low copy numbers are currently unavailable. Thus, we aimed to develop universal primers applicable for all known RVFV strains. Based on the genome sequences available from public databases, we designed eight pairs of universal PCR primers covering the entire RVFV genome. To evaluate primer universality, four RVFV strains (ZH548, Kenya 56 (IB8), BIME-01, and Lunyo), encompassing viral phylogenetic diversity, were chosen. The nucleic acids of the test strains were chemically synthesized or extracted via cell culture. These RNAs were evaluated using the PCR primers, resulting in successful amplification with expected sizes (0.8–1.7 kb). Sequencing confirmed that the products covered the entire genome of the RVFV strains tested. Primer specificity was confirmed via in silico comparison against all non-redundant nucleotide sequences using the BLASTn alignment tool in the NCBI database. To assess the clinical applicability of the primers, mock clinical specimens containing human and RVFV RNAs were prepared. The entire RVFV genome was successfully amplified and sequenced at a viral concentration of 108 copies/mL. Given the universality, specificity, and clinical applicability of the primers, we anticipate that the RVFV universal primer pairs and the developed method will aid in RVFV phylogenomics and mutation detection.